Remaking Rwanda : state building and human rights after mass violence state building and human rights after mass violence - Scott Straus and Lars Waldorf; Straus, Scott, 1970-; Waldorf, Lars. (Madison, Wis. : The University of Wisconsin Press, 2011)
"In the mid-1990s, civil war and genocide ravaged Rwanda. Since then, the country's new leadership has undertaken a highly ambitious effort to refashion Rwanda's politics, economy, and society, and the country's accomplishments have garnered widespread praise. Remaking Rwanda is the first book to examine Rwanda's remarkable post- genocide recovery in a comprehensive and critical fashion. By paying close attention to memory politics, human rights, justice, foreign relations, land use, education, and other key social institutions and practices, this volume raises serious concerns about the depth and durability of the country's reconstruction."--Page 4 of cover.
Limitations to political reform : the undemocratic nature of transition in Rwanda / Timothy Longman -- Instrumentalizing genocide : the RPF's campaign against "genocide ideology" / Lars Waldorf -- The ruler's drum and the people's shout : accountability and representation on Rwanda's hills / Bert Ingelaere -- Building a Rwanda "fit for children" / Kirrily Pells -- Beyond "you're with us or against us" : civil society and policymaking in post-genocide Rwanda / Paul Gready -- Aid dependence and policy independence : explaining the Rwandan paradox / Eugenia Zorbas -- Funding fraud? : donors and democracy in Rwanda / Rachel Hayman -- Waging (civil) war abroad : Rwanda and the DRC / Filip Reyntjens -- Bad karma : accountability for Rwandan crimes in the Congo / Jason Stearns and Federico Borello -- Victor's justice revisited : Rwandan Patriotic Front crimes and the prosecutorial endgame at the ICTR / Victor Peskin -- The uneasy relationship between the ICTR and Gacaca / Don Webster -- The Sovu trials : the impact of genocide justice on one community / Max Rettig -- "All Rwandans are afraid of being arrested one day" : prisoners past, present, and future / Carina Tertsakian -- High modernism at the ground level : the Imidugudu policy in Rwanda / Catharine Newbury -- Rwanda's post-genocide economic reconstruction : the mismatch between elite ambitions and rural realities / An Ansoms -- The Presidential Land Commission : undermining land law reform / Chris Huggins -- The past is elsewhere : the paradoxes of proscribing ethnicity in post-genocide Rwanda / Nigel Eltringham -- r
Includes bibliographical references and index.
Keywords: Since 1994; Human rights -- Rwanda; Human rights; Politics and government; Rwanda -- History -- 1994-; Rwanda -- Politics and government -- 1994-; Rwanda; Rwanda; Rwanda -- historia -- 1990-talet -- sekelskiftet 2000.; Rwanda; History